Prevention procedures for nurses during the COVID epidemic in acute care hospital: Experiences from Republika Srpska - Knežević Darija; Trifunović Silvana; Dobrovoljski Daniela (Association of Nurses Technicians and Midwives, 2021)
The epidemic of the COVID-19 disease presented a great threat to the public health. The SARS-CoV-2 virus is still spreading on a global level, so the accurate global number of the infected or deceased from the COVID-19 disease is yet to be estimated or correctly counted. The nurses have always played a great role in the prevention and control of infections, isolations and public health protection. The nurses' work during the COVID-19 epidemic has created a history of nursing. Nurses have been on the front line of defense from the SARSCov-2 virus for over a year now and many of them are already on the edge of endurance, both mentally and physically. The professional security is the key for the work of nurses who are facing the danger of infection on a daily basis. The aim of this paper is to show the actions and measures taken by the nurses in Republika Srpska that could help in the decrease of the global transmission of the infection. Compared with some European countries and their fight with the epidemic, Republika Srpska has maintained the number of confirmed cases on a level which can be controlled. The prevention measures are the only thing that can stop the spread of this new infectious disease. In our biggest healthcare institution of a tertiary level, a large number of COVID procedures for nurses and other healthcare workers have been released. Nurses are, together with other healthcare professionals, actively involved in the interventions around the COVID-19 and will be one of the key factors that will stop the pandemic.